Gendering Environmental Assessment: Women’s Participation and Employment Outcomes at Voisey’s Bay - Cox, David; Mills, Suzanne (ARCTIC, 2015)
This paper examines the effect of Inuit and Innu women’s participation in environmental assessment (EA) processes on EA recommendations, impact benefit agreement (IBA) negotiations, and women’s employment experiences at Voisey’s Bay Mine, Labrador. The literature on Indigenous participation in EAs has been critiqued for being overly process oriented and for neglecting to examine how power influences EA decision making. In this regard, two issues have emerged as critical to participation in EAs: how EA processes are influenced by other institutions that may help or hinder participation and whether EAs enable marginalized groups within Indigenous communities to influence development outcomes. To address these issues we examine the case of the Voisey’s Bay Nickel Mine in Labrador, in which Indigenous women’s groups made several collective submissions pertaining to employment throughout the EA process. We compare the submissions that Inuit and Innu women’s groups made to the EA panel in the late 1990s to the final EA recommendations and then compare these recommendations to employment-related provisions in the IBA. Finally we compare IBA provisions to workers’ perceptions of gender relations at the mine in 2010. Semi-structured interviews revealed that, notwithstanding the recommendations by women’s groups concerning employment throughout the EA process, women working at the site experienced gendered employment barriers similar to those experienced by women in mining elsewhere. We suggest that the ineffective translation of EA submissions into EA regulations and the IBA, coupled with persistent masculinity within the mining industry, weakened the effect of women’s requests for a comprehensive program to hire and train Indigenous women. Dans cet article, nous nous penchons sur la participation des femmes inuites et innues aux processus d’évaluations environnementales (EE) et sur l’effet de cette participation sur les recommandations des EE, les négociations relatives à l’entente sur les répercussions et les ...